Scientific facts behind creatine monohydrate as sport nutrition supplement - Silber, M. L. (The Journal of Sports Medicine and Physical Fitness, 1999)
Currently, strong efforts are being made toward demonstrating possible risks of using pure creatine monohydrate (Cr.H2O). In this article, scientific facts and considerations are presented, which support such concern. A further attempt is made to pursue the concept of possible risks of uncontrolled supplementation in athletes with pure Cr.H2O. The problem is viewed from the scientific evidence that a highly conservative mechanism of homeostatic feed-back inhibitory self-regulation of Cr biosynthesis in the body has been evolutionary developed. It is shown that numerous features characteristic to Cr biosynthesis, metabolism, and regulation allow to interpret its stimulatory action in the body as endocrine hormone-like. Based on this assumption, a practical approach for detecting altered links in Cr metabolism and biosynthesis under conditions of pure Cr.H2O overdosing, is suggested. Strategic considerations regarding early diagnosis, prognosis, and correction of the down-regulated endogenous Cr biosynthesis in athletes on continuous pure Cr.H2O supplementation, are discussed. As a high efficient and safe alternative to pure Cr.H2O, a complex nutrition supplement formula for elite athletes is proposed, which exploits natural alpha-ketoglutarate as a vehicle for delivering exogenous low molecular biologically-active compounds, including Cr.